Verification processor for SAR calibration and interferometry - Shimada, M (Advances in space research, 1999)
This paper presents a verification processor which can be used for imaging, calibration, and interferometry of data from a spaceborne synthetic aperture radar (SAR). This system can process the SAR on board ERS-1 and JERS-1 with various types of the computers ranging from microcomputers to the supercomputers. This paper summarizes the functionality, configuration, and system performance of the processor.